Financing Biofuel Through Green Sukuk Corporate: Stage, Potential, and Maturity (JEJAK: Jurnal Ekonomi dan Kebijakan, 2023)
Climate mitigation and adaptation policy financing have emerged as a critical topics in climate discussions. Effective financing schemes are often debated as potential mitigation measures, with the proceeds going toward adaptation activities. This research aims to investigate the viability of green sukuk corporate as a source of financing for biofuel development initiatives in Indonesia. A forecasting process, indexation, and early warning system (EWS) method are used to test the model to assess possible risks at a specific maturity level. In this study, factor variables include GDP, Inflation, the Jakarta Islamic Index (JII), sukuk corporate outstanding, and accumulated sukuk corporate issued. The main findings of this study suggest that to generate sustainable biofuel finance, three-stage models/concepts must be built; the commitment to business as usual, the greenhouse gas mitigation stage, and the debt repayment stage. In terms of potential, the trend of green corporate sukuk is toward greater participation by sovereigns and non financial corporations. In terms of maturity, corporate green sukuk requires a longer repayment period than conventional bonds, with a time tenor of 3–5 years being suitable. Finally, we show that the issuance of green corporate sukuk is supported by macroeconomic stability. The bond scheme can be repaid and carried out to provide sustainable benefits for renewable energy.